Wii, Kinect, & Move. Heart rate, oxygen consumption, energy expenditure, and ventilation due to different physically active video game systems in college students. - Scheer, K. C.; Siebrandt, S. M.; Brown, G. A.; Shaw, B. S.; Shaw, I. (International Journal of Exercise Science, 2014)
Nintendo Wii, Sony Playstation Move, and Microsoft XBOX Kinect are home video gaming systems that involve player movement to control on-screen game play. Numerous investigations have demonstrated that playing Wii is moderate physical activity at best, but Move and Kinect have not been as thoroughly investigated. The purpose of this study was to compare heart rate, oxygen consumption, and ventilation while playing the games Wii Boxing, Kinect Boxing, and Move Gladiatorial Combat. Heart rate, oxygen consumption, and ventilation were measured at rest and during a graded exercise test in 10 males and 9 females (19.8 ± 0.33 y, 175.4 ± 2.0 cm, 80.2 ± 7.7 kg,). On another day, in a randomized order, the participants played Wii Boxing, Kinect Boxing, and Move Gladiatorial Combat while heart rate, ventilation, and oxygen consumption were measured. There were no differences in heart rate (116.0 ± 18.3 vs. 119.3 ± 17.6 vs. 120.1 ± 17.6 beats/min), oxygen consumption (9.2 ± 3.0 vs. 10.6 ± 2.4 vs. 9.6 ± 2.4 ml/kg/min), or minute ventilation (18.9 ± 5.7 vs. 20.8 ± 8.0 vs. 19.7 ± 6.4 L/min) when playing Wii boxing, Kinect boxing, or Move Gladiatorial Combat (respectively). Playing Nintendo Wii Boxing, XBOX Kinect Boxing, and Sony PlayStation Move Gladiatorial Combat all increase heart rate, oxygen consumption, and ventilation above resting levels but there were no significant differences between gaming systems. Overall, playing a "physically active" home video game system does not meet the minimal threshold for moderate intensity physical activity, regardless of gaming system.